A motivação da prática de musculação sob a perspectiva bioecológica - Lemos Filho, Joacks de Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Motivation is a very important component that is present in the physical exercise practices. The resistance training can be conceptualized as an activity where motivational behavior is deeply linked. The resistance training practice has expanded in modern society, this way, it's essential understand which are the motivational factors that attract the human being to this context. This research objectified identifying the motivational aspects that lead to the resistance training practice, endorsed by the bioecological theory of human development of Urie Bronfrenbenner. This construct conceptualizes that the human development is lineate by the individual's interaction with his closest environments in the course of life and time. This interaction promotes changes and adaptions in many areas, such as, for example, the motivational. The developed research is about an exploratory study, grounded by a bibliographic research. The addressed literature was designated by SciELO and Google Academic's databases, published between 2011 and 2016. Were selected 12 documents that comply with the inclusion criteria, 8 national articles and 4 national monographs. From the research, it was possible to identify that the most reasons cited by the resistance training practitioners was health and aesthetics. The review by the bioecological perspective enabled characterize the resistance training as a microsystem, which suffers influences from the macrosystems present on society, as media and social values. Thus, the macro contexts attributes influence the individual's closest environment, consequently your behavior and development
Keywords: Musculação; Motivação (Psicologia); Exercícios físicos